PENGATURAN PEMENUHAN HAK PILIH AKTIF PENYANDANG TUNA NETRA DALAM PENYELENGGARAN PEMILIHAN UMUM YANG BERLANDASKAN ASAS KERAHASIAAN - Farhans Darenra; Emilda Firdaus; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
A person with visual impairment is any person who has limited vision dueto one thing or another who in interacting with the environment experiencesobstacles and difficulties to participate fully and effectiveli in the socialenvironment of the community. In the general election process in Indonesia,people with visual impairments have difficulty in giving their voting rights due touneven access to raised letters at polling stations designated for blind people, inpractice in the field blind people who are part of persons with disabilities cannotvote independently because more than the 20.000 polling stations at the time ofthe 2019 general election did not provide embossed access for Template BrailleThis research is a normative legal research, it is based on literatureresearch which referst to the contens of reading books or supporting books thathave a corelation with the background of the problem to be studied. This studyuses secondary date sources consisting of primary, secondary, and tertiary legalmaterials. This study uses qualitative date analysis by producing a deductivemethod of drawing conclusions, namely drawing conclusions from that aregeneral to things that are specific.From the result of the discussion, it can be concluded that law number 7 of2017 concerning general elections does not clearly regulate the state’s obligstionto guarantee the fulfillmen of access for blind people in voting at polling stationsduring the general election. The practice that then occured actually gave accessfor other people to participate in helping blind person choose the candidate theywhoulf choose which indirectly that person would know who the candidate chosenby the blind person was, this clearly violates the principle of confidentiality ingenera.